STRESS FIELDS REVEALED BY AFTERSHOCKS OF THE STRONGEST EARTHQUAKES OF TIEN SHAN - O. A. Kuchay; Z. A. Kalmet’eva; M. E. Kozina; K. E. Abdrakhmatov (Геодинамика и тектонофизика)
This study focused on the state of stress in the aftershock areas of the strongest earthquakes registered in Tien Shanon 11 August 1974 (MS=7.3), 24 March 1978 (MS=7.1), 01 November 1978 (MS=6.8), 19 August 1992 (MS=7.3), and 05 October 2008 (MS=6.9). These earthquakes occurred in similar geodynamic conditions in the zone of the nearly N–S oriented compression caused by the India-Eurasia collision. The parameters of the state of stress were determined by Yu.L. Rebetsky method of cataclastic analysis (MCA) of displacements on faults, based on the focal mechanisms of aftershocks. In the first stage of MCA, we determined the orientations of the principal stress axes, the Lode-Nadai coefficients, and the geodynamic types of the state of stress in the study area. The stress fields reconstructed from the aftershocks of different energy levels show that the principal deviatoric stress axes pattern becomes less orderly as the magnitude of seismic events decreases. A peculiar feature of the aftershock process is the misalignment of the axes of maximum compression in the mechanisms of the weakest aftershocks and the compression axis in the focal mechanism of the main seismic event. Most of the aftershocks were recorded west of the location of the main earthquake.